Impacto de la conformación de las unidades educativas en la convivencia escolar de los estudiantes - Cortez Gavilanes, Tatiana Elizabeth (2018)
The New Model of Educational Management is a project created to guarantee and ensure compliance with the right to education, in order to influence directly on universal access and with equity to caring, quality education. Nevertheless the students have had problems when the new educational model was applied especially in coexistence, so to achieve a good co-living it is very important that each institution obtain an effective code of coexistence to get better the relations between the whole educational community, that‟s why the purpose of this research has been to determine the importance of knowing and applying the coexistence code through diagnostic and bibliographic research to improve the interrelations among the students of the educational institution;. The methodological procedure was applied to obtain bibliographic information and data collection to diagnose the true situation in the institution, for which three specific objectives have been established: analyze the theoretical foundations of the impact of educational units and school coexistence; apply the methodological process for the acquisition of data and information for the development of the project; and synthesize the results of the data and information collection to establish conclusions and recommendations. The methodology of the research was: logical research methods: the scientific method to establish the approach of the problem and the formulation of the problem, the inductive, deductive, analytical and synthesize method that allowed to analyze and synthesize the information from primary and secondary bibliographic sources; the particular research methods: the descriptive, historical and statistical method; The research techniques used were: observation and survey with their respective instruments. The impact is of a social and academic nature because when talking about coexistence, it refers to the good relations that must exist between all the members of an educational community, something that is very important to achieve with the stated objective.